Exploration of the Chemical Space of DNA‐encoded Libraries. Issue 6 (28th January 2022) - Pikalyova, Regina; Zabolotna, Yuliana; Volochnyuk, Dmitriy M.; Horvath, Dragos; Marcou, Gilles; Varnek, Alexandre
Abstract: DNA‐Encoded Library (DEL) technology has emerged as an alternative method for bioactive molecules discovery in medicinal chemistry. It enables the simple synthesis and screening of compound libraries of enormous size. Even though it gains more and more popularity each day, there are almost no reports of chemoinformatics analysis of DEL chemical space. Therefore, in this project, we aimed to generate and analyze the ultra‐large chemical space of DEL. Around 2500 DELs were designed using commercially available building blocks resulting in 2, 5B DEL compounds that were compared to biologically relevant compounds from ChEMBL using Generative Topographic Mapping. This allowed to choose several optimal DELs covering the chemical space of ChEMBL to the highest extent and thus containing the maximum possible percentage of biologically relevant chemotypes. Different combinations of DELs were also analyzed to identify a set of mutually complementary libraries allowing to attain even higher coverage of ChEMBL than it is possible with one single DEL. Abstract :